2003
DOI: 10.1016/s0895-7061(03)01012-4
|View full text |Cite
|
Sign up to set email alerts
|

Blunted nocturnal fall in blood pressure and left ventricular mass in elderly individuals with recently diagnosed isolated systolic hypertension

Abstract: An association between blunted nocturnal SBP fall and increased LVM was observed in the early phases of ISH in the elderly. This finding may have important prognostic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The normal variation in BP is a dipping pattern characterized by a 10% to 20% dip in BP from day to night (3,42). Individuals with a less than 10% reduction in BP during sleep are described as having a nondipping BP pattern (2,24,38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal variation in BP is a dipping pattern characterized by a 10% to 20% dip in BP from day to night (3,42). Individuals with a less than 10% reduction in BP during sleep are described as having a nondipping BP pattern (2,24,38).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies involving subjects with uncomplicated essential hypertension have revealed an association between a nondipper BP profile and an increased risk of target organ damage at the cardiac, renal, vascular and cerebrovascular levels (6,9,10,15,18,27,28,(42)(43)(44)(45). Target organ damage has also been found to be linked with two additional abnormal BP patterns: reverse dipping (nocturnal rise in night-time BP) and extreme dipping (nocturnal fall in night-time BP of greater than 20%) (46).…”
mentioning
confidence: 99%
“…Among the others, non-dippers also showed high baPWV, whereas no marked difference was observed between extreme dippers and dippers ( Table 1). The mechanism underlying the relationship between blunted nocturnal BP drop and MCI may thus differ somewhat with that of extreme dippers, that is, advanced arteriosclerosis and cerebral arterial remodeling in risers and non-dippers, 34 and cerebral hypoperfusion due to the nocturnal BP fall in extreme dippers. 28,35 Recently, excessive sympathetic activation was represented to be a factor potentially responsible for the day-night BP difference.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with this decline in nocturnal BP are known as "dippers", and those who experience a blunted decline in nocturnal BP are known as "non-dippers" [2]. Several studies involving subjects with uncomplicated essential hypertension have revealed an association between the non-dipper BP profile and increased risk of target organ damage at the cardiac, vascular and cerebrovascular levels [3,4].…”
Section: Introductionmentioning
confidence: 99%